ACM Honors Distinguished Members for Contributions to Computing. (Communications of the ACM, 2006)
The article presents a list of recipients of the ACM Distinguished Members award, a newly created recognition program that honors individuals for their contributions to the practical and theoretical aspects of computing and information technology. The category was created by the ACM in 2006 as a complement to its Fellows program, which was established in 1993 to recognize AMC members. A list of individuals who have solved problems in industries including computer security, robotics, and mobile computing is presented.